Survival and Prognosis for Malignant Tumors of Odontogenic Origin. (29th March 2016) - Agarwal, Sunil; Mark, Jonathan; Xie, Changchun; Ghulam, Enas; Patil, Yash
Abstract : Objective: Determine survival and factors affecting survival for patients with malignant tumors of odontogenic origin. Study Design: Retrospective analysis of the National Cancer Institute's SEER database (Surveillance, Epidemiology, and End Results). Setting: Tertiary medical center. Subjects and Methods: All cases of malignant tumors of odontogenic origin were extracted from the SEER database for the period of 1973 to 2011. Demographic, tumor‐specific, and survival data were tabulated and Kaplan‐Meier survival analysis conducted according to histopathologic results. Cox regression analysis stratified for histopathology was conducted to determine factors that influenced survival. Results: A total of 308 cases of malignant tumors with odontogenic origin were analyzed. Malignant ameloblastoma accounted for 59.7% of cases, followed by malignant odontogenic tumor (35.4%; including odontogenic carcinoma, odontogenic sarcoma, primary intraosseous carcinoma, and ameloblastic carcinoma) and ameloblastic fibrosarcoma (2.9%). The overall mean and median were 229 and 227 months, respectively, while the 5‐year survival rate was 81% for the entire cohort. Malignant ameloblastoma exhibited the best mean survival (237 months), whereas malignant odontogenic tumor (139 months) and ameloblastic fibrosarcoma (42 months) had lower mean survival rates. Younger age, surgery with adjuvant radiation, and smaller tumor size were found to improve survival. Conclusions: Significantly different survival can be expected depending on individual tumor histopathology, tumor size, age at diagnosis, and treatment modality.